The Development Status, Challenges and Countermeasures of Investment Banks in China - Xu, Yongdong (Asia Pacific Economic and Management Review, 2025)
This paper conducts an in-depth examination of the development status of investment banks in China, analyses existing challenges, and proposes corresponding countermeasures. Through a review of relevant literature, it outlines the developmental trajectory, business models, and market competition landscape of Chinese investment banks. Drawing upon practical case studies and data analysis, it identifies deficiencies in risk management, innovation capabilities, and talent cultivation within the sector. Finally, it proposes countermeasures to promote the sustainable development of Chinese investment banks, focusing on improving the regulatory framework, strengthening innovation-driven approaches, and enhancing talent quality.